The conceptualizations of adolescence constructed by professionals within the family health strategy (FHS) - Débora Cristina Fonseca; Sérgio Ozella (Faculdade de Medicina de Botucatu (Unesp), 2010)
This paper examines the meanings constructed around adolescence, withtheir implications for the practices of physicians and nurses working within theFamily Health Strategy (FHS) in amunicipality in the interior of the State ofSão Paulo. The analysis was based oninterviews and showed that immobilityregarding collective actions wasreinforced by predominance of a natural,universal and pathological view thatpositioned adolescence at a place notwithin the work routine of family healthteams. For this reason, there is a need torethink the conceptualizations, startingfrom the position that these professionalsoccupy in the labor market.